2013
DOI: 10.2147/ijwh.s47710
|View full text |Cite
|
Sign up to set email alerts
|

HPV infection, cervical abnormalities, and cancer in HIV-infected women in Mumbai, India: 12-month follow-up

Abstract: BackgroundHIV-infected women are at a higher risk of cervical intraepithelial neoplasia (CIN) and cancer than women in the general population, partly due to a high prevalence of persistent human papillomavirus (HPV) infection. The aim of the study was to assess the burden of HPV infection, cervical abnormalities, and cervical cancer among a cohort of HIV-infected women as part of a routine screening in an urban overpopulated slum setting in Mumbai, India.MethodsFrom May 2010 to October 2010, Médecins Sans Fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
19
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 27 publications
14
19
4
Order By: Relevance
“…We found that the prevalence of genital HPV infection in the HIV-uninfected and HIV-infected women was similar to previously reported rates in Romania 3, 15, 16 , and similar to rates reported HIV-infected women in a multicenter European study 17 and other studies from limited resource countries 7, 18 . HIV infection in this group of Romanian women has had a different course in comparison to vertically infected children, with a natural history of 8–10 years of asymptomatic infection, similar to adults.…”
Section: Discussionsupporting
confidence: 90%
“…We found that the prevalence of genital HPV infection in the HIV-uninfected and HIV-infected women was similar to previously reported rates in Romania 3, 15, 16 , and similar to rates reported HIV-infected women in a multicenter European study 17 and other studies from limited resource countries 7, 18 . HIV infection in this group of Romanian women has had a different course in comparison to vertically infected children, with a natural history of 8–10 years of asymptomatic infection, similar to adults.…”
Section: Discussionsupporting
confidence: 90%
“…Pap smear abnormalities in HIV‐infected women have been reported from various studies in India to be varying from 6.3% to 19% . There was a higher prevalence of Pap smear abnormalities in our study of 27.5%.…”
Section: Discussioncontrasting
confidence: 55%
“…In our study, the prevalence of HPV infection among HIV‐infected women was 57.7%. Studies done in India have found a varying prevalence of 26.4% to 56% . High‐risk HPV types are reportedly found in 37.3–59% of patients with HIV .…”
Section: Discussionmentioning
confidence: 99%
“…This data corroborate previous reports [46,47]. However, this rate is much lower than the rates reported in sub-Saharan Africa, which ranged from 49.8% to 73% [48] and India (27.5%) [15].…”
Section: Discussionsupporting
confidence: 91%